Battery electrolyte additive and application thereof
By adding collagen derivatives to the electrolyte of aqueous zinc ion batteries, the problems of zinc dendrites and side reactions are solved, the cycle life and coulomb efficiency of the battery are improved, and environmentally friendly electrochemical performance improvement is achieved.
Patent Information
- Application Number
- CN202411915667.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
The uncontrollable dendrites growth and water-induced side reactions during the charging and discharging process of aqueous zinc ion batteries, which hinder their commercial application.
Collagen derivatives are introduced as additives in the electrolyte solution, and through its rich polar groups interact with zinc ions, it guides the uniform deposition of zinc ions and inhibits dendrites.
It effectively solves the problems of zinc dendrites and corrosion, improves the cycle life and Coulomb efficiency of aqueous zinc ion batteries, and at the same time, the use of natural biological materials has achieved environmentally friendly electrochemical performance improvement.
Smart Images

Figure CN119812510A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a battery electrolyte additive and application thereof. Background Art
[0002] In order to meet the needs of sustainable development, people have an increasing demand for electrical energy storage, which has promoted the research and development of new battery systems. So far, lithium-ion batteries still dominate the field of energy storage due to their high energy density and long cycle life. However, the current shortage of resources and the safety and environmental pollution problems caused by organic electrolytes have greatly hindered the further large-scale application of lithium-ion batteries. Therefore, batteries composed of more abundant elements (such as Na, K, Mg, Al, Zn, Ca, Fe) have attracted widespread attention. Among them, aqueous zinc-ion batteries (AZIBs) benefit from the low cost, inherent safety and high specific energy density (820mAh g) of the zinc anode. -1 and 5,855mAh cm -3 ), which has been developing rapidly in recent years.
[0003] However, the successful commercialization of AZIBs is hampered by the uncontrollable dendrite growth and water-induced side reactions of the zinc anode during the charge and discharge process. In recent years, a variety of strategies have been proposed to optimize the zinc anode, including electrolyte engineering, anode surface coating, anode structure design, and separator modification. Among them, electrolyte additives are one of the electrolyte optimization methods. Because they can avoid the problems of complex preparation process, excessive ineffective weight, and high manufacturing cost, they are considered to be a promising method for commercialization.
[0004] Additive engineering can effectively solve the problems of negative electrode side reactions and zinc dendrites, guide the uniform deposition of zinc ions, and thus inhibit the formation of dendrites. A large number of different types of electrolyte additives have been studied, mainly divided into two types: inorganic additives and organic additives. Compared with inorganic substances, organic materials have the advantages of a wide variety, low cost, designable structure, and rich functional groups. In addition, various organic molecules have been proven to play an outstanding role in stabilizing Zn negative electrodes in recent years.
[0005] Adding a large amount of organic additives can easily reduce the deposition kinetics of the zinc negative electrode, and flammable additives increase the risk of actual use of the battery. Therefore, the development of a non-polluting, environmentally friendly, safe, widely available, low-cost, and efficient biomolecular electrolyte additive is of great significance for improving the electrochemical performance of aqueous batteries and their commercial application. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a battery electrolyte additive and application thereof.
[0007] The present invention also aims to introduce a small amount of collagen derivative additives into the aqueous electrolyte to improve the electrochemical performance of the aqueous battery, including the cycle performance and coulombic efficiency, by protecting the zinc negative electrode.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A battery electrolyte additive, characterized in that:
[0010] The battery electrolyte additive is a collagen derivative;
[0011] The mass concentration of the battery electrolyte additive in the electrolyte is 0.03-30 mg / mL.
[0012] Furthermore, the collagen derivative is collagen hydrolyzate.
[0013] Furthermore, the characteristic unit structure of the collagen hydrolysate is: Gly-Xaa-Yaa
[0014] Wherein, Gly is glycine;
[0015] Xaa is one of proline, glycine, alanine, valine, leucine, isoleucine, methionine (methionine), hydroxyproline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, aspartic acid, glutamic acid, lysine, arginine or histidine;
[0016] Yaa is mostly one of hydroxyproline, glycine, alanine, valine, leucine, isoleucine, methionine (methionine), proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, aspartic acid, glutamic acid, lysine, arginine or histidine.
[0017] Furthermore, in the characteristic unit structural formula of the collagen hydrolysate, the mass ratio of Gly:Xaa:Ya is 15-32:4-10:2-9.
[0018] The invention also discloses a battery electrolyte, which comprises zinc salt, water and the battery electrolyte additive.
[0019] Furthermore, the mass ratio of the zinc salt to the battery electrolyte additive is 32-485:0.03-30.
[0020] Further, the zinc salt is one or more of zinc sulfate, zinc chloride, zinc trifluorosulfonate and zinc bromide;
[0021] The zinc salt concentration is 0.2-3 mol / L.
[0022] Furthermore, the pH value of the battery electrolyte is 3-6.
[0023] The invention also discloses an application of the battery electrolyte additive in aqueous battery electrolyte.
[0024] In the present invention, the water used in the electrolyte can be deionized water or ultrapure water.
[0025] The mechanism of the present invention is:
[0026] As an eco-friendly natural product, collagen derivative additives are relatively cheap and contain abundant amino / carboxyl / hydroxyl groups (-NH 2 , -COOH, -OH) and other polar groups.
[0027] The present invention firstly utilizes the abundant polar groups in the collagen derivative additive as active sites for interacting with metal ions to facilitate the conduction of zinc ions. At the same time, the electronegativity of the lone pair of electrons carried by the amino-containing N atom in the molecule makes the amino-containing side of the molecule more inclined to adsorb on the surface of the zinc negative electrode and guide the diffusion of zinc ions as a zinc-philic site.
[0028] In addition, the hydroxyl group in the molecule faces the electrolyte, which can limit the free water molecules near the negative electrode, effectively solving problems such as zinc dendrites and corrosion, thereby improving the cycle life and coulombic efficiency of aqueous zinc-ion batteries.
[0029] The present invention has the following beneficial effects:
[0030] 1. The battery electrolyte of the present invention can effectively solve the problems of zinc dendrites and corrosion, thereby improving the cycle life and coulombic efficiency of aqueous zinc ion batteries.
[0031] 2. The raw material collagen hydrolyzate in the battery electrolyte of the present invention is derived from natural biological materials, and has the advantages of being non-toxic, highly biocompatible, environmentally friendly, having abundant raw material sources, and being rich in a variety of effective functional groups. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The implementation results of the present invention will be further described below in conjunction with the accompanying drawings.
[0033] Figure 1 The surface deposition of 1 mAh cm on the SEM zinc negative electrode in Example 1 of the present invention -2 SEM image of zinc foil after zincification, where Figure 1 (A) is the result of Comparative Example 1, Figure 1 (B) is the result of Example 1;
[0034] Figure 2This is a plane SEM image of the zinc foil after zinc is deposited and stripped on the surface of the SEM zinc negative electrode in Example 1 of the present invention, wherein Figure 2 (A) is the result of Comparative Example 1, Figure 2 (B) is the result of Example 1. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0036] In the embodiments of the present invention, unless otherwise defined, all professional terms used hereinafter have the same meanings as those generally understood by those skilled in the art.
[0037] Unless otherwise specified, various reagents and raw materials used in the present invention can be purchased from the market.
[0038] Example 1
[0039] This embodiment provides a collagen derivative additive electrolyte additive
[0040] The additive used is collagen hydrolysate.
[0041] Among them, the concentration of collagen hydrolysate is 0.3mg / mL.
[0042] Collagen hydrolysate is composed of glycine, proline and hydroxyproline in a molar ratio of approximately 17:6:5.
[0043] 28.756 g of zinc sulfate heptahydrate was dissolved in deionized water and stirred magnetically until the solution was clear. Then, the solution was fixed to volume with a 50 mL volumetric flask to obtain a 2 mol / L basic zinc sulfate electrolyte with a pH of 3.65.
[0044] Add collagen hydrolyzate to the zinc sulfate electrolyte, stir until the powder is dissolved, and let it stand for later use.
[0045] An aqueous zinc ion symmetric battery was assembled using zinc foil as positive and negative electrodes and glass fiber as a separator.
[0046] In Table 1, the symmetric cell at 1 mA cm -2 、1mAh cm -2 and 5mA cm -2 、5mAh cm -2 Under these conditions, a stable time-voltage curve was obtained, in which the polarization voltage did not show obvious fluctuations, indicating its stable cycling performance.
[0047] Compared with Comparative Example 1, 2 mol / L ZnSO 4 The cycle life of the symmetrical battery with 0.3 mg / mL collagen hydrolysate electrolyte system is more than 2200 h at 5 mA cm-2 、5mAh cm -2 Under the given conditions, it can reach more than 1200h.
[0048] The electrolyte system containing collagen hydrolysate additive was subjected to one zinc deposition / stripping.
[0049] like Figure 1 As shown, the SEM image of the zinc negative electrode surface shows that its surface remains flat and smooth.
[0050] In the electrolyte of Comparative Example 1, the SEM image of the zinc negative electrode surface showed an uneven morphology, indicating that the collagen hydrolyzate additive can induce uniform zinc deposition.
[0051] Zinc stripping results such as Figure 2 As shown, the SEM image of the zinc negative electrode surface shows that the zinc negative electrode surface is relatively flat and smooth with fewer grooves, while in the electrolyte of Comparative Example 1, the SEM image of the zinc negative electrode surface exhibits an uneven morphology, which is not conducive to subsequent uniform zinc deposition.
[0052] Example 2
[0053] This embodiment provides a collagen derivative additive electrolyte additive:
[0054] The additive used is collagen hydrolysate.
[0055] Among them, the concentration is 30 mg / mL, and the molar ratio of hydroxyproline, lysine, and phenylalanine is approximately 12:4:3.
[0056] Dissolve 2.875 g of zinc sulfate heptahydrate in deionized water, stir magnetically until the solution is clear, and dilute to volume with a 50 mL volumetric flask to obtain a 0.2 mol / L basic zinc sulfate electrolyte with a pH of 6.
[0057] Add collagen hydrolyzate to the zinc sulfate electrolyte, stir until the powder is dissolved, and let it stand for later use.
[0058] An aqueous zinc ion symmetric battery was assembled using zinc foil as positive and negative electrodes and glass fiber as a separator.
[0059] In Table 1, the symmetrical battery has a -2 、1mAh cm -2 and 5mA cm -2 、5mAh cm -2 Under the same conditions, a stable time-voltage curve was obtained, in which the polarization voltage did not show obvious fluctuations, indicating its stable cycle performance. 4 The cycle life of the symmetric battery in the electrolyte system of 0.3 mg / mL collagen hydrolysate is 1 mA cm-2 、1mAh cm -2 Under the condition of more than 2000h, at 5mA cm -2 、5mAh cm -2 Under the given conditions, it can reach more than 900h.
[0060] Example 3
[0061] This embodiment provides a collagen derivative additive electrolyte additive:
[0062] The additive used is collagen hydrolysate.
[0063] Among them, its concentration is 0.03 mg / mL, and the molar ratio of glycine, hydroxyproline and arginine is approximately 15:4:2.
[0064] Dissolve 54.529 g of zinc trifluorosulfonate in deionized water, stir magnetically until the solution is clear, and dilute to volume with a 50 mL volumetric flask to obtain a 3 mol / L basic zinc trifluorosulfonate electrolyte with a pH of 3.
[0065] Add collagen hydrolyzate to the above zinc trifluorosulfonate electrolyte, stir until the powder is dissolved, and let stand for later use.
[0066] An aqueous zinc ion half-cell was assembled using zinc foil as the negative electrode, copper foil as the positive electrode and glass fiber as the separator.
[0067] In order to explore the effect of collagen hydrolysate additive on the stability of zinc anode, a Zn / / Cu half-cell was assembled and the plating / stripping behavior of zinc electrode in electrolyte was studied.
[0068] Compared with Comparative Example 2, at 2 mol / L ZnSO 4 In the Zn / / Cu / / collagen hydrolysate electrolyte, the Zn / / Cu half-cell exhibited more than 550 stable plating / stripping cycles, and the Coulombic efficiency was stable at 99.60% from 20 to 550 cycles (Table 2). The stable cycling and high Coulombic efficiency are attributed to the inhibitory effect of collagen hydrolysate on dendrite growth and side reactions.
[0069] Example 4
[0070] This embodiment provides a collagen derivative additive electrolyte additive:
[0071] The additive used is collagen hydrolysate.
[0072] Among them, the concentration is 0.3 mg / mL, and the molar ratio of glycine, proline, and hydroxyproline is approximately 32:10:9.
[0073] Dissolve 54.529 g of zinc trifluorosulfonate in deionized water, stir magnetically until the solution is clear, and dilute to volume with a 50 mL volumetric flask to obtain a 3 mol / L basic zinc trifluorosulfonate electrolyte with a pH of 3.
[0074] Add collagen hydrolyzate to the above zinc trifluorosulfonate electrolyte, stir until the powder is dissolved, and let stand for later use.
[0075] An aqueous zinc ion half-cell was assembled using zinc foil as the negative electrode, copper foil as the positive electrode and glass fiber as the separator.
[0076] In order to explore the effect of collagen hydrolysate additive on the stability of zinc anode, a Zn / / Cu half-cell was assembled and the plating / stripping behavior of zinc electrode in electrolyte was studied.
[0077] Compared with Comparative Example 2, at 2 mol / L ZnSO 4 In the electrolyte of Zn / / Cu / ...
[0078] Comparative Example 1
[0079] Dissolve 28.756 g of zinc sulfate heptahydrate in deionized water, stir magnetically until the solution is clear, and dilute to volume with a 50 mL volumetric flask to obtain a 2 mol / L basic zinc sulfate electrolyte.
[0080] An aqueous zinc ion symmetric battery was assembled using zinc foil as positive and negative electrodes and glass fiber as a separator.
[0081] In Table 1, the symmetrical battery has a -2 、1mAh cm -2 and 5mA cm -2 、5mAh cm -2 Under these conditions, the time-voltage curve was obtained. 2mol / L ZnSO 4 The cycle life of the symmetric battery in the electrolyte system is 1 mA cm -2 、1mAh cm -2 Under the condition of more than 150h, at 5mA cm -2 、5mAh cm -2 Under the given conditions, the test time can reach more than 70h.
[0082] Comparative Example 2
[0083] Dissolve 36.353 g of zinc trifluorosulfonate in deionized water, stir magnetically until the solution is clear, and dilute to volume with a 50 mL volumetric flask to obtain a 2 mol / L basic zinc trifluorosulfonate electrolyte.
[0084] An aqueous zinc ion half-cell was assembled using zinc foil as the negative electrode, copper foil as the positive electrode and glass fiber as the separator, and the electroplating / stripping behavior of the zinc electrode in the electrolyte was studied.
[0085] In Table 2, in 2 mol / L zinc trifluorosulfonate electrolyte, the coulombic efficiency of the Zn / / Cu half-cell dropped sharply after only 200 cycles.
[0086] The test results of cycle life and cycle number are detailed in Table 1 and Table 2:
[0087] Table 1 shows the cycle life of symmetrical batteries assembled with the electrolyte containing no additives in Comparative Example 1 and the electrolyte containing additives in Example 1 and Example 2;
[0088] Table 2 shows the cycle times of half-cells assembled from the electrolyte of Comparative Example 2 without additives and the electrolytes of Examples 3 and 4 with additives.
[0089] Table 1
[0090]
[0091] Table 2
[0092]
[0093] The present invention relates to a battery electrolyte additive and its application, wherein the battery electrolyte additive is a collagen hydrolyzate, and the mass concentration of the battery electrolyte additive in the electrolyte is 0.03-30 mg / mL. The battery electrolyte of the present invention comprises a zinc salt, water and a battery electrolyte additive. The additive of the present invention can effectively solve the problems of negative electrode side reactions, zinc dendrites and the like in aqueous zinc ion batteries, guide the uniform deposition of zinc ions, and thus inhibit the generation of dendrites. The raw material collagen hydrolyzate in the battery electrolyte of the present invention is derived from natural biomaterials, and has the advantages of being non-toxic, highly biocompatible, environmentally friendly, having abundant raw material sources, and being rich in a variety of effective functional groups.
[0094] The above embodiments show and describe the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for illustrating the principles of the present invention, and are not intended to limit the scope of the present invention in any way. Without departing from the scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the protection claimed.
Claims
1. A battery electrolyte additive, characterized in that: The battery electrolyte additive is a collagen derivative; The mass concentration of the battery electrolyte additive in the electrolyte is 0.03-30 mg / mL.
2. The battery electrolyte additive according to claim 1, characterized in that: The collagen derivative is collagen hydrolyzate.
3. The battery electrolyte additive according to claim 2, characterized in that: The characteristic unit structural formula of the collagen hydrolysate is: Gly-Xaa-Yaa Wherein, Gly is glycine; Xaa is one of proline, glycine, alanine, valine, leucine, isoleucine, methionine (methionine), hydroxyproline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, aspartic acid, glutamic acid, lysine, arginine or histidine; Yaa is mostly one of hydroxyproline, glycine, alanine, valine, leucine, isoleucine, methionine (methionine), proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, aspartic acid, glutamic acid, lysine, arginine or histidine.
4. The battery electrolyte additive according to claim 3, characterized in that: In the characteristic unit structural formula of the collagen hydrolysate, the mass ratio of Gly:Xaa:Ya is 15-32:4-10:2-9.
5. A battery electrolyte, characterized in that: The battery electrolyte comprises zinc salt, water and the battery electrolyte additive according to any one of claims 1 to 4.
6. The battery electrolyte according to claim 5, characterized in that: The mass ratio of the zinc salt to the battery electrolyte additive is 32-485:0.03-30.
7. The battery electrolyte according to claim 5, characterized in that: The zinc salt is one or more of zinc sulfate, zinc chloride, zinc trifluorosulfonate and zinc bromide; The zinc salt concentration is 0.2-3 mol / L.
8. The battery electrolyte according to claim 5, characterized in that: The pH value of the battery electrolyte is 3-6.
9. Use of the battery electrolyte additive according to any one of claims 1 to 4 in aqueous battery electrolyte.